Optimal Location of Wind Turbines in a Wind Farm using Genetic Algorithm - C.Balakrishna Moorthy; M.K. Deshmukh; Darshana Mukherejee (Institute of Advanced Engineering and Science, 2014)
In the present study, genetic algorithm has been used to resolve the placement of wind turbines in a wind park giving maximum power and efficiency with minimum number of turbines. Unlike past approaches where each plot was subdivided into smaller square grids at the centre of which a turbine can be placed, the present study does not require division of the plot. Thus, a turbine now has more flexibility to be placed anywhere outside a radius of 200m of each other yielding better results. The case of unidirectional uniform wind is considered and 600 individuals evolve 3000 generations. Along with the optimal layout, fitness value, total power output, efficiency and number of turbines have also been reported. Comparison with results of earlier study and possible explanation is also provided.